Investigation of Changes in Liver Fibrosis Scores and Kidney Function in Patients with Diabetic Hepatosteatosis - Canbolat, Oytun; Karahisar Şirali, Semahat; Bulucu, Mehmet Fatih (The European Research Journal, 2026)
Objective: Hepatosteatosis, diabetes, and chronic kidney disease are significant risk factors for mortality and morbidity. The objective of this study was to examine the relationship between non-invasive liver fibrosis scores and kidney function tests in patients with diabetic hepatosteatosis. Methods: This present study was conducted through a retrospective analysis of two consecutive data sets of 72 diabetic patients aged 18–80 years of both sexes who were investigated for at our hospital between 2018 and 2024. The relationships between hepatosteatosis, diabetes mellitus parameters, kidney function tests, liver function tests, and fibrosis scores (BARD, BAAT, NFS, FIB4, APRI) were examined. Results: Among the patients included in the study, 54.2% (n=39) were female, and the mean age was 60.99±12.46 years. A moderate negative correlation was found between the initial GFR and both initial FIB4 (P<0.001) and NFS values (P=0.001), while a weak negative correlation was observed between the final GFR and both final FIB4 (P=0.016) and NFS values (P=0.001). A weak negative association was observed between the differences in the initial and final GFR values and both the differences in BARD scores and BARD ratios (P=0.039). Linear regression analysis revealed that a one-unit increase in the BARD ratio led to a 4.34-unit decrease in GFR. Conclusion: The study revealed a correlation between fibrosis progression, as measured by repeated measurements, and an increased risk of developing new-onset chronic kidney disease. The findings of this study indicated that liver fibrosis in patients with diabetic hepatosteatosis might contribute to the development of chronic kidney disease, thereby underscoring the necessity for enhanced monitoring of kidney function.